Training the Navigator Workforce: A Bachelor of Science in Patient Navigation. - Cleveland, Nina; Tapp, Lauren (Journal of Oncology Navigation & Survivorship, 2026)
Introduction: Patient navigation (PN) is a growing profession rooted in the field of oncology. Despite the demonstrated need for additional educational programs, only 2 bachelor's-level PN programs currently exist (Georgia Gwinnett College and Misericordia University). This paper outlines the development and implementation of a bachelor's degree program in PN and aims to provide guidance for institutions seeking to develop a PN program. Methods: The establishment of a new PN degree was a multistage process requiring the consideration of several factors. Industry data were collected to determine the need for a PN program while institutional administration and stakeholders were consulted. Program outcomes and curriculum framework were developed in accordance with the standards set by the Professional Oncology Task Force as outlined in the Oncology Navigation Standards of Professional Practice. Prior to program approval and implementation, a thorough analysis of resources, including qualified faculty, was performed. Discussion: Developing the PN concentration required organizational planning and alignment with healthcare workforce needs, including roles in acute care and community-based settings. Strengths identified included engaging faculty, curriculum relevance, experiential learning, and emphasis on collaborative care and compassion. Recognized areas of improvement were organization within courses, professional development opportunities, and more challenging practicum experiences. Implementation barriers found were limited personnel, faculty credentialling, and misunderstanding of PN as a profession. Conclusion: Detailed planning and consideration of industry climate and institutional resources have resulted in marked program growth. As the major continues to evolve, expansion of internship opportunities and professional development will be prioritized.